Reactive Perforating Collagenosis in an Indian Child with Down’s Syndrome: A Rare Case Report - Sushil Rathi; Dharmendra Mishra; Shraddha P Kote; Sharad Vairalkar (Indian Journal of Paediatric Dermatology)
Perforating dermatoses are a heterogeneous group of disorders characterized by transepidermal elimination of materials from dermal connective tissue. It is classified into four primary dermatoses – Kyrle’s disease, perforating folliculitis, reactive perforating collagenosis (RPC), and elastosis perforans serpiginosa. It is known to be associated with various acquired and inherited systemic disorders. Here, we report a rare case of RPC in a 4-year-old Indian child with Down’s syndrome.